Systematic Analysis of the Biochemical Characteristics of Activated Sludge During Ozonation for Lowering of Biomass Production. (4th March 2017) - Ren, Hongyang; Ma, Lingli; Wang, Bing; Gong, Hang; Yuan, Zeng; Li, Zhenzhen
ABSTRACT: Properties of activated sludge during ozonation were analyzed. The structure and surface characteristics altered with the increase of ozone dosage. At low ozone dosage, the floc structure was completely dismantled. Floc fragments reformed through reflocculation at an ozone dosage greater than 0.20 g O3 ·g −1 mixed liquor suspended solids (MLSS). Inactivation of microorganisms in the activated sludge mixture was caused by ozonation. Microbial growth decreased by up to 65% compared to the control. Simultaneously, 92.5% of nucleotide and 97.4% of protein in microbial cells of the sludge were released. Organic substance, nitrogen and phosphorus were released from the sludge during the ozonation process. The initial value of soluble chemical oxygen demand (SCOD) was 72 mg·L −1 . When the ozone dosage was 0.12 g O3 ·g −1 MLSS, the value of SCOD rapidly reached 925 mg·L −1, increased by almost 12-fold. Simultaneously, 54.7% of MLSS was reduced. The composition of MLSS was changed, indicating that the inner water of cells and volatile organic substance decreased during the ozonation process.